Transmembrane Batten Disease Proteins Interact With a Shared Network of Vesicle Sorting Proteins, Impacting Their Synaptic Enrichment - Rechtzigel, Mitchell J.; Meyerink, Brandon L.; Leppert, Hannah; Johnson, Tyler B.; Cain, Jacob T.; Ferrandino, Gavin; May, Danielle G.; Roux, Kyle J.; Brudvig, Jon J.; Weimer, Jill M. (Frontiers in Neuroscience, 2022)
Batten disease is unique among lysosomal storage disorders for the early and profound manifestation in the central nervous system, but little is known regarding potential neuron-specific roles for the disease-associated proteins. We demonstrate substantial overlap in the protein interactomes of three transmembrane Batten proteins (CLN3, CLN6, and CLN8), and that their absence leads to synaptic depletion of key partners (i.e. SNAREs and tethers) and altered synaptic SNARE dynamics, demonstrating a novel shared etiology.